An overview on ethnobotanico-pharmacological studies carried out in Morocco, from 1991 to 2015: Systematic review (part 1) - Fakchich, Jamila; Elachouri, Mostafa (Journal of ethnopharmacology, 2021)
The full bibliometric records of data retrieved from ethnobotanical field studies carried out in Morocco (1991–2015) was quali-quantitatively analysed. Despite the importance of traditional medicinal uses in Morocco, any comments about the methodologies and approaches adopted by reviewed studies have been undertaken. Include more data about the importance of traditional medicinal uses in Morocco. Three key points were targeted in this review: (i) to contribute to original compilation of medicinal plants traditionally used by people at whole Morocco, by gathering and documenting the current status of these ancestral medical practices, (ii) to provide a novel insight into the relationship between local and biomedical disease concepts in Moroccan society, taking into account health-related beliefs, and their influences on medicinal plant uses, (iii) to figurout the weaknesses and the strengths of the conceptual approches and methods adopted by researchers in ethnobotanical field works. With the help of a computerized database querying, we conducted an extensive literature search respecting our integration criteria. We performed this bibliographic research by using the following search engines available over the Web: Google Scholar, PUBMED, Sciencedirect, Current Content Connect, SCOPUS, SPRINGER LINK, GLOBAL PLANTS, Cochrane Library and SCIRUS. The scientific names listed in the present paper have been validated according to the “The Plant List” and the African Plants Database in order to standardize ethnobotanical data on an international level. For the analysis of data gathered, quali-quantitative analyses have been performed. A total of 905 medicinal plant species belonging to 116 families and 726 genera have been selected from 63 published articles. The dominant families were ASTERACEAE (111 species) followed by the FABACEAE (77 species), LAMIACEAE (75 species) and APIACEAE (46 species). The plant species listed are used to cure several public ailments. The digestive ailments represented the most important category (494 species) followed by dermatological diseases (407 species), diabetes (315 species) and urinary diseases (277 species). We assigned the importance of the plant species by several measures (including Frequency Cited (FC), Number of Uses (NU), Number of Respondents (NR) and Index of Performance (IP). The ICF (Informant Consensus Factor) calculated was important in all categories of diseases averaging 47%. The results obtained, which cover the whole country, delineate the profile of rich wealth of indigenous knowledge on traditional uses of medicinal plants heald by Moroccan society. The total number of 905 plant species listed in this paper, are currently being utilized as medicines and the number is expected to grow as infrastructure allows greater access to unexplored parts of the country. Furthermore, the know how, regarding the plants used, is consistent because the ICF has recorded important values for most diseases treated. Furthermore, in the present paper, we suggested, for authors, some useful recommendations for ethnobotanical field works such as the respect of ethnobotanical standards including checklist of plants with international data base, the deposited voucher specimens, sampling and collection methods. [Display omitted]